The nutritional profile and quality of life of cirrhosis patients without encephalopathy at Hospital Selayang/ Syahrul Bariah Abdul Hamid and Nurul Azra Roslan - Abdul Hamid, Syahrul Bariah; Roslan, Nurul Azra (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Prevalence of malnutrition was 63.0% and 18.3% in cirrhotic and non-cirrhotic patients, respectively and is correlated with the increased of mortality and morbidity among cirrhotic patients. This study aimed to investigate the relationship between nutritional profile and quality of life of cirrhosis patients without encephalopathy at Hospital Selayang. 28 cirrhosis patients without encephalopathy were recruited in this cross-sectional study. Descriptive analysis was deployed to evaluate the nutritional profile and quality of life. The mean age, BMI, calorie and protein intake, and albumin of the patients were 53.14 ± 8.51 years, 22.19 ± 4.60 kg/m², 19.21 ± 7.84 kcal/kg/day, 0.60 ± 0.32 g/kg/day and 2.45 ± 0.52 mg/dL respectively. 78.6% of them were in SGA score B. Quality of life of the patients was poor as presented on most domains. There was a significant (p<0.05) with negative fair correlation (r= -0.417) between SGA score and physical functioning. There also a significant (p<0.05) with negative fair correlation (r= -0.389) was found between SGA score and vitality. The nutrient intake and quality of life of the patients was poor. Further research is needed on the development of nutrition screening tool and updated nutritional recommendation for cirrhosis patients without encephalopathy for the improvement in nutritional status and quality of life